AB1234 MICRO-RNA 155 AND MIR-34A: POSSIBLE BIOMARKERS OF INFLAMMATORY BURDEN AND DISEASE ACTIVITY IN ANCA-ASSOCIATED VASCULITIS WITH RENAL INVOLVEMENT. (13th June 2020) - Bruno, D.; Cerasuolo, P. G.; Di Mario, C.; Bosello, S. L.; Gigante, L.; Musto, A.; Vischini, G.; Costanzi, S.; Alivernini, S.; Tolusso, B.; Grandaliano, G.; Gremese, E.
Abstract : Background: Predicting clinical outcomes in ANCA-related glomerulonephritis remains a major challenge. To date, there is no reliable biomarker able to predict renal prognosis in patients with ANCA-associated vasculitis (AAV). Micro-RNA (miRNA) are non-coding RNAs involved in the fine tuning of immune cells biology and this epigenetic modulation associates with different phenotypes and prognosis in several diseases. Objectives: To investigate the expression of miR-155 and miR-34a in kidney biopsies of AAV patients according with renal outcome. Methods: Fifteen patients with AAV and renal involvement (mean age 63.0 ±13.3 years, disease duration 4.9±2.2 months), who underwent renal biopsy. Demographic, clinical and autoimmune parameters were recorded for each patient. Each kidney biopsy was classified according to the Berden Classification, Risk group (according to the ANCA Renal Risk Score) and the chronicity Classification of the Mayo Clinic's proposed score. MiR-155 and miR-34a expression was investigated on kidney biopsy tissue using the miRNeasy FFPE kit (Qiagen). The quantitative expression of miR-155, miR-34a and housekeeping gene U1, used as control, was assessed by Real Time-PCR. MiR-155 and miR-34a expression was correlated with histopathological and clinical-laboratory parameters. Each patient was followed for 12 months and renal outcome was considered according to KDIGO CKD Classification. Markers of inflammation (ESR, CRP) and urine analysis data were recorded at baseline and after 12 months. Results: Six (40%) patients were p-ANCA positive and 9 (60%) c-ANCA positive. Eight patients (53%) also had pulmonary involvement. The mean baseline GFR was 30.7±28.8 ml/min/1.73 m 2 and 10 patients (66%) showed an active urinary sediment. At disease onset, the mean expression of miR-155 was 9.5±21.1, while the expression of mir-34a was 13.1±46.2. Considering the autoimmune profile, kidney tissue of p-ANCA positive patients was enriched of mir-155 (19.6±30.6 fold) compared to c-ANCA positive patients (1.9±2.9 fold; p=0.001). Particularly, considering the renal function, kidney tissue of patients with greater impairment of renal function ( KDIGO stage 5 ) was enriched of miR-155 (21.5±38.3 fold) compared to patients with less renal impairment ( KDIGO stage 1-4 ) (4.72±8.16 fold, p=0.004). Tissue expression of miR-155 and miR-34a did not correlated with the abovementioned histopathological classifications. After 12 months from kidney biopsy, 3(20%) patients had a worsening of renal function, 5 (33%) still presented elevated markers of inflammation and 3 (20%) still had proteinuria at urine analysis. At baseline, kidney tissue of patients with higher CRP plasma levels and proteinuria at follow-up presented higher expression of miR-155 (p=0.002 and p=0.001), whereas no significant differences were found about miR-34a kidney tissue expression. Conclusion: MiRNAs may play a potential role in the pathogenesis of ANCA-related glomerulonephritis. MiR-155 kidney enrichment seems to mirror the disease inflammatory burden and activity at the onset and after 12 months representing a possible biomarker in ANCA vasculitis with renal involvement. This finding may represent the basis for further studies on miRNA expression in blood samples, aiming to identify a non-invasive biomarker of kidney damage, predicting disease's relapses and patients' prognosis. References: [1]Renauer et al, Clin Rev Allergy Immunol. 2016 Disclosure of Interests: Dario Bruno: None declared, Pier Giacomo Cerasuolo: None declared, Clara Di Mario: None declared, Silvia Laura Bosello Speakers bureau: Abbvie, Pfizer, Boehringer, Laura Gigante: None declared, Alessia Musto: None declared, Gisella Vischini: None declared, Stefano Costanzi: None declared, Stefano Alivernini: None declared, Barbara Tolusso: None declared, Giuseppe Grandaliano: None declared, Elisa Gremese Speakers bureau: Abbvie, BMS, Celgene, Jannsen, Lilly, MSD, Novartis, Pfizer, Sandoz, UCB